Absolute configuration and biological profile of pyrazoline enantiomers as MAO inhibitory activity. Issue 1 (23rd November 2018) - Goksen, Umut Salgin; Sarigul, Sevgi; Bultinck, Patrick; Herrebout, Wouter; Dogan, Ilknur; Yelekci, Kemal; Ucar, Gulberk; Gokhan Kelekci, Nesrin
Abstract: A new racemic pyrazoline derivative was synthesized and resolved to its enantiomers using analytic and semipreparative high‐pressure liquid chromatography. The absolute configuration of both fractions was established using vibrational circular dichroism. The in vitro monoamine oxidase (MAO) inhibitory profiles were evaluated for the racemate and both enantiomers separately for the two isoforms of the enzyme. The racemic compound and both enantiomers were found to inhibit hMAO‐A selectively and competitively. In particular, the R enantiomer was detected as an exceptionally potent and a selective MAO‐A inhibitor ( K i  = 0.85 × 10 −3  ± 0.05 × 10 −3  μM and SI: 2.35 × 10 −5 ), whereas S was determined as poorer compound than R in terms of K i and SI (0.184 ± 0.007 and 0.001). The selectivity of the enantiomers was explained by molecular modeling docking studies based on the PDB enzymatic models of MAO isoforms. Abstract :